2022
DOI: 10.3389/fpsyg.2022.942252
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors of Tourist Expenditure: Neglected or Negligible?

Abstract: Despite recent progress in identifying the factors of tourist expenditure, knowledge of the psychological characteristics of tourists is necessary to fully understand their impact. Therefore, this study attempts to extend the economic, sociodemographic and trip-related factors by including psychological factors in the econometric models. A total of 1,036 Slovak tourists who paid for summer holidays abroad in the summer of 2021 were interviewed. Three of the six psychological factors analysed (two stable person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Additionally, Brida and Scuderi (2013) review 86 publications during the period of 1977–2012, confirming that tourism expenditure has mostly been modeled using tourists’ socioeconomic and trip-specific characteristics as exogenous determinants and highlighting the scarcity of studies incorporating psychological attributes. Consequently, relevant aspects such as satisfaction, travel motives, and personality traits have more frequently been incorporated in recent contributions, (Alfarhan et al, 2022a; Bernini and Galli 2022; Lam-González et al, 2021; Perles-Ribes et al, 2021; Štefko et al, 2022). Their review also recognizes innovation in modeling as a challenging future direction, along with further attempts to support the theoretical assumptions underlying modeling exercises.…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Brida and Scuderi (2013) review 86 publications during the period of 1977–2012, confirming that tourism expenditure has mostly been modeled using tourists’ socioeconomic and trip-specific characteristics as exogenous determinants and highlighting the scarcity of studies incorporating psychological attributes. Consequently, relevant aspects such as satisfaction, travel motives, and personality traits have more frequently been incorporated in recent contributions, (Alfarhan et al, 2022a; Bernini and Galli 2022; Lam-González et al, 2021; Perles-Ribes et al, 2021; Štefko et al, 2022). Their review also recognizes innovation in modeling as a challenging future direction, along with further attempts to support the theoretical assumptions underlying modeling exercises.…”
Section: Literaturementioning
confidence: 99%
“…Vetitnev (2015) also finds that length of stay mediates the effects of source of payment, satisfaction, income, accommodation, and resort type on total personal tourism expenditure, whereas travel distance, party size, and holiday organization mode only exert direct effects on spending in the Russian resort industry. Also, Štefko et al (2022) investigate the impact of psychological characteristics on expenditure levels using data on outbound Slovak tourists. The authors find that attributes such as spending propensity, tightwad, and thrift do not influence expenditure levels directly, and that length of stay mediates the effect of tightwad, at best, weakly.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…They became more available due to the steep development of IT products and innovative solutions in business process support (Roshchyk et al, 2022;Straková et al, 2022). Although there are many factors including social, cultural, or economic ones that affect expenditures (Stefko et al, 2022b), firms having more R&D productivity and high value become less likely to go bankrupt (Bai & Tian, 2020). Furthermore, firms lacking innovative abilities are more likely to go bankrupt than innovative firms (Donkor et al, 2018).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…According to the UNWTO (United Nation World Tourism 2008), tourist expenditure is the amount paid by tourist for consuming goods and services and valuable objects, for own use or for gifts, before and during tourist visits. Previous studies also explain that psychological factors have a tendency to influence the willingness to spend, in addition to income level, trip type, family size and length of stay (Štefko, Džuka, and Lačný 2022), and motivation has a significant effect on tourist shopping decisions (Juniawan 2023). Mudarra-Fernández et al (2019) found that socio-economic variables influence the decision of tourists to spend, variables related to the characteristics of the trip, the destination and the psychological of the tourist.…”
Section: Introductionmentioning
confidence: 98%